RELATIONSHIP OF TEACHER COMPETENCY TO THE QUALITY OF STUDENTS - Mubarok, Mochamad Wildan (Abjadia : International Journal of Education, 2024)
This research examines the relationship between teacher competence and the quality of students in secondary schools. Teacher competency, which includes pedagogical knowledge, teaching skills, and professional attitudes, is considered a key factor in determining the quality of education. This research uses a qualitative descriptive method with a correlational approach, and data was collected through literature study. The results of the analysis show that teacher competence has a significant influence on the quality of students in various aspects, including academic achievement, social skills, emotional well-being and moral development. Strong pedagogical competence in teachers is correlated with increased student academic achievement, while teacher personality and social competence plays an important role in developing students' social skills and morality. These findings support previous literature which emphasizes the importance of teacher competence in education. This research suggests that teacher professional development programs should focus more on strengthening all aspects of competency to improve the quality of education holistically. The implications of this research are highly relevant for policy makers and educational practitioners in designing more effective interventions to improve educational outcomes.